Curtain of death [large type] : a clandestine operations novel - Griffin, W. E. B.; Butterworth, William E. (William Edmund) (Griffin, W. E. B. Clandestine operations novel., 2017)
January 1946: Two WACs leave an officers club in Munich, and four Soviet NKGB agents kidnap them at knifepoint in the parking lot and shove them in the back of an ambulance. That is the agents first mistake, and their last. One of the WACs, a blond woman improbably named Claudette Colbert, works for the new Directorate of Central Intelligence, and three of the men end up dead and the fourth wounded. The incident, however, will send shock waves rippling up and down the line and have major repercussions not only for her, but for her boss, James Cronley, Chief DCI-Europe, and for everybody involved in their still-evolving enterprise. For, though the Germans may have been defeated, Cronley and his company are on the front lines of an entirely different kind of war now. The enemy has changed, the rules have changed and the stakes have never been higher.